Strategi Coping Stress dalam Menangani Stres Kerja Geriatric Nursing di PPSLU Mappakasunggu Kota Parepare - Saleh, Adnan Achiruddin; Amelia, Nur Resky (Institut Agama Islam Negeri Parepare, 2022)
This study aims to determine the effect of dialog reading methods and improve language skills of early childhood. This study used a single subject research with A-B design. The research subjects were students of Kindergarten A PAUD Anak Ceria Surabaya with information about the development of language skills which were known based on observations, interviews, language proficiency checklists, and formal tests regarding language development of children aged 4 years. Data obtained through analysis of the subject's language skills in baseline (A) with intervention conditions (B) and analysis between baseline (A) and intervention (B). The results showed an increase in children's language skills from 34.3% in baseline to 65.7% in the intervention. The conclusion from this age study shows that the dialogue reading method can improve children's language skills. The implication of this research is that the dialogue reading method can stimulate the improvement of children's language skills as early as possible and for children who have developed language development, especially expressive language. The dilaog reading method can be applied at home and at school.